PENGARUH KEMAMPUAN KEUANGAN DAERAH TERHADAP PENYELENGGARAAN OTONOMI DAERAH DI KABUPATEN HALMAHERA UTARA - Widadari, Krisya; Rares, Joyce Jacinta; Dengo, Salmin (Sam Ratulangi University, 2016)
ABSTRACT Research is moving on from the early observations that the existence of symptomsdecrease acceptance of original income area (PAD) the effect on the low success ofthe Organization of the autonomous region, particularly in North Halmahera Regency. Thus, this research aims to know the ada-tidaknya the influence of Regional financial capability against the success of the Organization of the autonomous region of North Halmahera Regency. Methods of descriptive and quantitative approaches used to solve problems in this research. A simple random sample set as many as 60 employees at the same time as the respondent. Data collection is done with the interview techniques, observation and documentation in order to capture data and secondary data promer. To analyze the data applied statistical methods descriptive statistics and inferensial with the technique of percentage, simple linear regression and correlation. Research results show that the positive effect of the regional financial capabilities and significantly to the success of the Organization of the Autonomous Region of North Halmahera Regency with the degree of determination of 92.7%. However, the ability of the financial area of North Halmahera Regency still categorised